2016
DOI: 10.1104/pp.16.01581
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Membrane H+-ATPase AHA1 Plays a Major Role in Stomatal Opening in Response to Blue Light

Abstract: (K.-i.S.).Stomata open in response to a beam of weak blue light under strong red light illumination. A blue light signal is perceived by phototropins and transmitted to the plasma membrane H + -ATPase that drives stomatal opening. To identify the components in this pathway, we screened for mutants impaired in blue light-dependent stomatal opening. We analyzed one such mutant, provisionally named blus2 (blue light signaling2), and found that stomatal opening in leaves was impaired by 65%, although the magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 57 publications
11
90
0
Order By: Relevance
“…Plasma membrane H + -ATPases (AHAs) generate the protonmotive force across the plasma membrane necessary to activate ion and metabolite transport (Morsomme & Boutry, 2000). AHAs also play a pivotal role in the opening of stomata, which are important entry sites for bacteria during natural infection (Yamauchi et al, 2016). We found that RPS2 activation resulted in C-terminal dephosphorylation of AHA1 at T948 and at homologous sites of AHA2 (T947) and AHA4 (T955) (Figs 2, S2a; Tables 1, S4).…”
Section: Rps2 and Fls2 Activation Results In Dephosphorylation Of H +mentioning
confidence: 99%
“…Plasma membrane H + -ATPases (AHAs) generate the protonmotive force across the plasma membrane necessary to activate ion and metabolite transport (Morsomme & Boutry, 2000). AHAs also play a pivotal role in the opening of stomata, which are important entry sites for bacteria during natural infection (Yamauchi et al, 2016). We found that RPS2 activation resulted in C-terminal dephosphorylation of AHA1 at T948 and at homologous sites of AHA2 (T947) and AHA4 (T955) (Figs 2, S2a; Tables 1, S4).…”
Section: Rps2 and Fls2 Activation Results In Dephosphorylation Of H +mentioning
confidence: 99%
“…Note that BLUS1 expression is specific to guard cells and is not involved in the other phototropin-mediated responses, such as phototropism, chloroplasts movements, and leaf flattening (Takemiya et al, 2013a), suggesting that BLUS1 defines signaling specificity of stomatal opening among the phototropin-mediated responses. The signal generated by BLUS1 finally activates the PM H + -ATPase, mainly isoform AHA1, in guard cells through phosphorylation of a penultimate Thr in the C terminus with subsequent binding of a 14-3-3 protein Hayashi et al, 2011;Yamauchi et al, 2016).…”
Section: Blue Light Signaling For Stomatal Openingmentioning
confidence: 99%
“…Dominant mutants of AHA1, a major H + -ATPase isoform in Arabidopsis, ost2-1D and ost2-2D, displayed constitutively open stomatal phenotypes, because dominant mutations cause constitutive activity of H + -ATPase (Merlot et al, 2007). More recently, it was reported that loss-of-function mutants of AHA1 showed reduced blue light-induced stomatal opening (Yamauchi et al, 2016) and a closed stomatal phenotype (Osakabe et al, 2016). Furthermore, a lossof-function mutant of OSA7, a major PM H + -ATPase isoform in rice, also showed reduced blue light-induced increase of stomatal conductance (Toda et al, 2016).…”
Section: Involvement Of Pm H + -Atpase In Stomatal Openingmentioning
confidence: 99%
“…Blue light also inhibits S‐type anion currents in guard cells of wild‐type Arabidopsis, but not in the phototropin phot1/2 type BL receptor mutants (Marten et al ., ). These results demonstrate that blue light inhibits plasma membrane anion channels, whereas others found that it stimulates the guard cell plasma membrane proton pump autoinhibited H + ‐ATPase 1 (AHA1; Shimazaki et al ., ; Kinoshita & Hayashi, ; Yamauchi et al ., ). Preventing anions (negative charges) from leaving the cell and activating the outwardly directed H + pumps will result in a more negatively charged, hyperpolarized, guard cell membrane potential.…”
Section: Multisensory Guard Cells Integrate Abiotic and Biotic Signalmentioning
confidence: 99%